What are the main barriers to healthy eating among families? A qualitative exploration of perceptions and experiences of Tehranian men. (1st June 2015) - Farahmand, Maryam; Amiri, Parisa; Ramezani Tehrani, Fahimeh; Momenan, Amir Abbas; Mirmiran, Parvin; Azizi, Fereidoun
Highlights: We explored barriers to a healthy eating in Tehranian families experienced by men. "Modernization" and "Communication and modeling" are among the main barriers. "Personal factors" and "Lack of access" are the other barriers. The results could contribute to the designing of appropriate, related interventions. Abstract: Despite women playing a pivotal role in shaping nutritional patterns in their families, it is the men whose ideas and preferences, after children, influence the selection and consumption of daily foods among Iranian families. This study focused on exploring the main barriers to healthy eating as experienced by male participants of the Tehran Lipid Glucose Study (TLGS). A grounded theory approach was used for analyzing participants' experiences and their perceptions regarding these barriers. Participants were 98 men, aged 25–65 years, selected and recruited from the TGLS cohort. Data collection was conducted through fourteen semi-structured focus group discussions, between 2008 and 2009. All interviews and focus group discussions were audio recorded and transcribed verbatim. Constant comparative analysis of the data was conducted manually according to the Strauss and Corbin analysis method. The most important barriers to healthy eating were: (i) Personal factors, which included two subthemes – lack of knowledge and personal taste, (ii) Communication and modeling included two subthemes – other individuals and media/advertisements; (iii) Modernization included two subthemes – nutrition transition and women's role; and (iv) Lack of access to healthy foods, which included four subthemes – Inadequate confidence, perceived risk, high cost and time limitations. Appropriate attention and prioritized policy-making to modify the socio-environmental barriers to healthy eating were explored in the current study, along with effective educational programs that could help to promote healthy eating among Iranian families.